1 Recce - The Night Belongs to Us - Esterhuyse, Abel (Scientia Militaria - South African Journal of Military Studies, 2019)
Combining the writing abilities of a seasoned literary author with the intricacies of a good military story is almost a guarantee for a good book. And this is precisely the case with 1 Recce – The night belongs to us. It is without doubt a well-written book and an outstanding read. The book fills a gap in the existing South African military historiography by documenting the story of the formation and building of 1 Reconnaissance Regiment of the former defence force to full operational capacity.